Evolution of bi-Gaussian surface parameters and sealing performance for a gas face seal under a low-speed condition. (April 2018) - Hu, Songtao; Huang, Weifeng; Shi, Xi; Peng, Zhike; Liu, Xiangfeng; Wang, Yuming
Abstract: A spiral groove gas face seal, serving as a typical non-contacting seal, commonly encounters face contact during a low-speed condition such as the startup, shutdown, barring and warming-up operations. By using a discrete manner, the surface-topography evolution of the two mated sealing rings during a low-speed barring process is achieved, and is in a great agreement with the previous standard tests. The bi-Gaussian surface-topography evolution is found to well identify the end running-in, material adhesion and deep scratches. Furthermore, the surface-topography evolution exhibits a high correlation with the recorded seal-performance indexes including leakage rate, torque and acoustic emission signal, which is helpful in exploring the deterioration mechanism of sealing performance. Highlights: Surface-topography evolution of a gas face seal under a low-speed condition is investigated. Seal-performance evolution including leakage rate, torque and acoustic emission is analyzed. Correlation between the above two evolutions is explored.